Induced Hyperproteinemia and Its Effects on the Remodeling of Fat Bodies in Silkworm, Bombyx mori - Chen, Xue-Dong; Wang, Yong-Feng; Wang, Yu-Long; Li, Qiu-Ying; Ma, Huan-Yu; Wang, Lu; Sima, Yang-Hu; Xu, Shi-Qing (Frontiers in Physiology, 2018)
Hyperproteinemia, which is characterized by an abnormally elevated plasma protein concentration (PPC), is a high-mortality, metabolic complication associated with severe liver and kidney disease. It is difficult to clinically distinguish the difference between the impacts of primary diseases and hyperproteinemia on tissues and organs, and there are no available animal models of hyperproteinemia. Here, we constructed an animal model of hyperproteinemia with a controllable PPC and no primary disease effects in the silkworm Bombyx mori that has attracted interest owing to its potential use in the pathological analysis of model animals. Silkworm have an open circulatory system in which each organ is directly immersed in hemolymph. The fat body (FB) of a silkworm, as a major organ for nutrient storage and energy metabolism, can effectively reflect hyperproteinemia-induced metabolic abnormalities in damaged visceral tissues. A pathogenesis study showed that hyperproteinemia attenuated cell autophagy and apoptosis by attenuating an endocrine hormone, thereby preventing FB remodeling during metamorphosis. Meanwhile, hyperproteinemia increased oxidative stress in the FB and resulted in a dysfunction of amino acid conversion. Supplementation with exogenous 20-hydroxyecdysone effectively mitigated the hyperproteinemia-mediated inhibition of FB remodeling.